Epidemiology of dry eye disease in Argentina - Marini, María C. (2024)
BackgroundTo evaluate the prevalence of dry eye disease (DED) and its associated risk factors in a sample of the Argentine population.MethodsA prospective cross-sectional population-based study was conducted in Argentina during April 2022 through an anonymous electronic survey that included participants aged 12 years old or older. The prevalence of symptomatic DED was evaluated using the Women's Health Study (WHS) dry eye questionnaire. In addition, a list of conditions possibly related to dry eye were evaluated in the questionnaire to assess the prevalence of potential risk factors. A multivariate logistic regression analysis was performed.Results10,812 subjects (mean age 44.1 ± 13.9, range 12–94 years old) answered the survey. Overall prevalence of DED was 42.1%. DED prevalence in women was 45.1% (3848 out of 8525) and in men was 30.8% (704 out of 2287). Risk factors were female sex (OR 2.78; p < 0.001), age > 60 years (OR 2.92), rheumatologic disease (OR 2.80, CI 1.62–3.13), use of digital screens for more than 6 h per day (OR 2.62; CI 1.43–2.80), glaucoma topical treatment (OR 2.05; CI 1.20–3.01), dysthyroidism (2.03; CI 1.48–2.51), and sleeping less than 7 h per day (OR 1.92; CI 1.30–2.51).ConclusionDED was found to be a prevalent condition among Argentine participants, the main risk factors were determined by sex, age, and especially those related to lifestyle in South America.